P.064 FIREFISH Part 1: 1-year results on motor function in infants with Type 1 spinal muscular atrophy (SMA) receiving risdiplam (RG7916). (5th June 2019) - Seabrook, TJ; Baranello, G; Servais, L; Day, JW; Deconinck, N; Mercuri, E; Klein, A; Darras, B; Masson, R; Kletzl, H; Cleary, Y; El-Khairi, M; et al.
Abstract : Background: SMA is characterized by reduced levels of survival of motor neuron (SMN) protein from deletions and/or mutations of the SMN1 gene. While SMN1 produces full-length SMN protein, a second gene, SMN2, produces low levels of functional SMN protein. Risdiplam (RG7916/RO7034067) is an investigational, orally administered, centrally and peripherally distributed small molecule that modulates pre-mRNA splicing of SMN2 to increase SMN protein levels.Methods: FIREFISH (NCT02913482) is an ongoing, multicenter, open-label operationally seamless study of risdiplam in infants aged 1–7 months with Type 1 SMA and two SMN2 gene copies. Exploratory Part 1 (n=21) assesses the safety, tolerability, pharmacokinetics and pharmacodynamics of different risdiplam dose levels. Confirmatory Part 2 (n=40) is assessing the safety and efficacy of risdiplam.Results: In a Part 1 interim analysis (data-cut 09/07/18), 93% (13/14) of babies had ≥4-point improvement in CHOP-INTEND total score from baseline at Day 245, with a median change of 16 points. The number of infants meeting HINE-2 motor milestones (baseline to Day 245) increased. To date (data-cut 09/07/18), no drug-related safety findings have led to patient withdrawal. No significant ophthalmological findings have been observed.Conclusions: In FIREFISH Part 1, risdiplam improved motor function in infants with Type 1 SMA.